Financial management theory and practice - Chandra, Prasanna (New Delhi Tata McGraw Hill, 2011)
b
Keywords: Construction Engineering and Management (ME-CE); Finance Management; FINANCIAL SYSTEM; FUNDAMENTAL VALUATION CONCEPTS